Hard carbon negative electrode material and preparation method thereof, negative electrode plate, sodium ion battery and power-related equipment
By mixing and grinding the starch raw materials with sugar and lignin and sintering, the hard carbon negative electrode materials are solved, and the problems of easy expansion, high production cost, low capacity and unsatisfactory Coulomb efficiency in the prior art are solved, and high capacity and good electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411920892.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing hard carbon anode materials are prone to expansion, have high preparation costs, low capacity, and are not ideal for Coulombic efficiency.
By mixing and grinding the starch raw material with sugar and lignin, a hard carbon negative electrode material is prepared to prevent the material from expanding during sintering, increase the carbon production rate, and create a closed air through sintering to increase the platform capacity.
The high capacity and good electrochemical performance of hard carbon anode material are achieved, with a capacity of up to 350.14mAh/g, a first-time efficiency of 86.90%, and a capacity retention rate of up to 90.22% during the 200-week cycle of 0.2C.
Smart Images

Figure CN119725522A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a hard carbon negative electrode material and a preparation method thereof, a negative electrode sheet, a sodium ion battery and electrical equipment. Background Art
[0002] In the research of sodium-ion batteries, carbon-based materials have become the preferred target for negative electrode materials of sodium-ion batteries due to their wide sources, rich resources, diverse structures and long life. Among them, graphite materials as negative electrode materials of sodium-ion batteries are difficult to form sodium-inserted graphite compounds. + It can be stored in graphite, resulting in the suppression of reversible capacity. Compared with graphite, non-graphitizable hard carbon and graphitizable soft carbon have higher capacity as negative electrode materials for sodium ion batteries, but soft carbon materials are prone to change in interlayer spacing when sodium ions undergo intercalation and deintercalation reactions, and graphitizable soft carbon is easily graphitized at high temperatures, which reduces the interlayer spacing and reduces the material's sodium storage capacity; while hard carbon materials have large interlayer spacing, more defects and vacancies, and have higher sodium storage capacity.
[0003] In the prior art, starch is used as raw material to prepare hard carbon negative electrode materials. It is easy to expand during sintering, resulting in a low carbon yield. The sintering steps are complicated, resulting in a high preparation cost of the hard carbon negative electrode material, which is not conducive to industrial production. The capacity of the obtained hard carbon material is also low and the coulomb efficiency is not ideal. Summary of the invention
[0004] The purpose of this application is to provide a hard carbon negative electrode material and a preparation method thereof, a negative electrode sheet, a sodium ion battery and electrical equipment, aiming to solve the problems of existing hard carbon negative electrode materials being easy to expand, high preparation cost, low capacity and unsatisfactory coulombic efficiency.
[0005] To achieve the above objectives, the present application provides a method for preparing a hard carbon negative electrode material, comprising:
[0006] The starch raw material is mixed and ground with sugar and lignin to obtain a precursor;
[0007] The precursor is sintered to obtain a hard carbon negative electrode material.
[0008] In some embodiments, the sugars include monosaccharides and / or disaccharides; the sugars include at least one of D-galactose, glucose, fructose, sucrose, and lactose.
[0009] In some embodiments, the mass ratio of the starch raw material, the sugar, and the lignin is (90-99):(1-5):(1-5).
[0010] In some embodiments, the mixing and grinding time is 1 h to 2 h; and / or the particle size of the precursor is 80 mesh to 400 mesh.
[0011] In some embodiments, the sintering temperature is 1000° C. to 1600° C., and the sintering time is 5 h to 24 h.
[0012] In some embodiments, the starch raw material includes at least one of potato starch, corn starch, tapioca flour, and pregelatinized starch; and / or the lignin is dealkalized lignin.
[0013] The present application also provides a hard carbon negative electrode material, which is prepared by the above-mentioned method for preparing the hard carbon negative electrode material.
[0014] The present application also provides a negative electrode sheet, comprising the above-mentioned hard carbon negative electrode material.
[0015] The present application also provides a sodium ion battery, comprising the above-mentioned negative electrode sheet.
[0016] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0017] Compared with the prior art, the beneficial effects of this application include:
[0018] The preparation method of the hard carbon negative electrode material provided in the present application uses starch, which is low in cost and widely available, as raw material. First, the starch raw material is ground and mixed with sugars and lignin, mainly to create sodium ion acceptance sites, prevent the material from expanding during the sintering process, and improve the carbon yield; then the ground and mixed materials are sintered, and closed spaces are created during the sintering process to increase the platform capacity; this is conducive to improving the electrochemical performance of the material. The preparation method obtains the required hard carbon negative electrode material after one pyrolysis, and the process is simple, the raw materials shrink, and it is easy to operate, which reduces the sintering cost and is suitable for large-scale process production.
[0019] The hard carbon negative electrode material provided in the present application, when used as the negative electrode material of a sodium ion battery, has a capacity of up to 350.14 mAh / g, an initial efficiency of 86.90%, and a capacity retention rate of up to 90.22% after 200 cycles at room temperature and 0.2C, showing good initial coulombic efficiency and cycle performance.
[0020] The sodium ion battery provided in this application, in view of the advantages of the above-mentioned hard carbon negative electrode material, improves the capacity and first coulombic efficiency of the sodium ion battery, expands the application scenarios of the sodium ion battery, and promotes the development of downstream industries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0022] Figure 1 A schematic diagram of a process for preparing a hard carbon negative electrode material of the present application;
[0023] Figure 2 is the charge and discharge curve of the hard carbon negative electrode material of Example 2;
[0024] Figure 3 This is a graph of 200 cycles of the hard carbon negative electrode material of Example 1. DETAILED DESCRIPTION
[0025] As used herein:
[0026] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0027] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0028] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0029] In these examples, parts and percentages are by mass unless otherwise indicated.
[0030] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0031] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0032] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0033] This application provides a method for preparing a hard carbon negative electrode material. Figure 1 ,include:
[0034] S100: Mixing and grinding starch raw materials with sugars and lignin to obtain a precursor;
[0035] S200: Sintering the precursor to obtain a hard carbon negative electrode material.
[0036] The preparation method of the hard carbon negative electrode material provided in the present application uses starch, which is low in cost and widely available, as raw material. First, the starch raw material is ground and mixed with sugars and lignin, mainly to create sodium ion acceptance sites, prevent the material from expanding during the sintering process, and improve the carbon yield; then the ground and mixed materials are sintered, and closed spaces are created during the sintering process to increase the platform capacity; this is conducive to improving the electrochemical performance of the material. The preparation method obtains the required hard carbon negative electrode material after one pyrolysis, and the process is simple, the raw materials shrink, and it is easy to operate, which reduces the sintering cost and is suitable for large-scale process production.
[0037] In some embodiments, the sugars in step S100 include monosaccharides and / or disaccharides.
[0038] Optionally, the sugar includes at least one of D-galactose, glucose, fructose, sucrose and lactose.
[0039] A small amount of sugar is used to coat the starch raw material. Due to the high specific surface area, pore structure and conductive properties of sugar, it can provide more energy storage space and fast ion transmission channels, thereby improving the electrochemical performance.
[0040] In some embodiments, the starch raw material in step S100 includes at least one of potato starch, corn starch, tapioca starch, and pregelatinized starch. Starch is used as a raw material, so that its production cost is low and it is easy to obtain.
[0041] In some embodiments, the lignin in step S100 is dealkalized lignin.
[0042] Both lignin and sugar are doped and coated in the first step. The purpose of lignin modification is to create sodium ion acceptance sites to prevent the material from expanding during sintering and increase the carbon yield; sugar coating is to create closed pores during sintering and increase platform capacity; it is beneficial to improve the electrochemical performance of the material. The two work together, and the effect of this application cannot be achieved by using them alone. A small amount of lignin can also increase the reaction rate and improve the stability of the hard carbon material.
[0043] Dealkaline Lignin (DL) is lignin extracted from natural plants and treated with a special process, and its bases have been removed. This treatment makes the molecular structure of dealkaline lignin more complex, and compared with non-dealkaline lignin, dealkaline lignin is more difficult to decompose in some applications. Non-dealkaline lignin is lignin extracted directly from original natural plants without any treatment. It has a simpler molecular structure and is more easily biodegradable.
[0044] In some embodiments, the mass ratio of starch raw material, sugar, and lignin in step S100 is (90-99):(1-5):(1-5), for example, it can be 90:1:1, 91:1:1, 92:1:1, 93:1:1, 94:1:1, 95:1:1, 96:1:1, 97:1:1, 98:1:1, 99:1:1, 95:2:3, 96:3:4, or it can be any ratio within the range of (90-99):(1-5):(1-5).
[0045] If the mass ratio of starch raw materials, sugars and lignin is lower than this range, the first coulombic efficiency of the hard carbon negative electrode material will be reduced. If the mass ratio of starch raw materials, sugars and lignin is higher than this range, the capacity of the hard carbon negative electrode material will be reduced.
[0046] In some embodiments, the mixing and grinding time in step S100 is 1 h to 2 h, for example, 1 h, 1.5 h, 2 h or any value between 1 h and 2 h.
[0047] In the specific implementation process, the modification process is accompanied by grinding, which can fully mix the starch raw materials with sugars and lignin to make the reaction more complete.
[0048] In some embodiments, the particle size of the precursor obtained in step S100 is 80 mesh to 400 mesh, for example, it can be 80 mesh, 90 mesh, 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh, 200 mesh, 210 mesh, 220 mesh, 230 mesh, 240 mesh, 250 mesh, 260 mesh, 270 mesh, 280 mesh, 290 mesh, 300 mesh, 350 mesh, 400 mesh or any value between 80 mesh and 400 mesh.
[0049] The layered structure of hard carbon and the presence of amorphous carbon phase can provide more catalytic active sites and adsorption sites, enhancing the catalytic activity and adsorption performance of hard carbon. Therefore, when designing and preparing hard carbon materials, it is necessary to reasonably control their particle size and structure to achieve the desired performance.
[0050] In some embodiments, the sintering temperature in step S200 is 1000℃~1600℃, for example, it can be 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃, 1550℃, 1600℃, or any value within the range of 1000℃~1600℃; the sintering time is 5h~24h, for example, it can be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, or any value within the range of 5h~24h.
[0051] When the sintering temperature is lower than 1000℃ or the time is less than 5h, the carbonization will be insufficient, the substances other than carbon cannot be volatilized, and the micropore structure cannot be improved and the activity cannot be increased. When the sintering temperature is higher than 1600℃ or the time is longer than 24h, the newly generated and enlarged pores in the carbonization process will collapse, affecting the electrochemical performance.
[0052] The sintering in step S200 is performed under a protective atmosphere, and the protective atmosphere includes argon and / or nitrogen.
[0053] The present application also provides a hard carbon negative electrode material, which is prepared by the above-mentioned method for preparing the hard carbon negative electrode material.
[0054] The hard carbon negative electrode material provided in the present application, when used as the negative electrode material of a sodium ion battery, has a capacity of up to 350.14 mAh / g, an initial efficiency of 86.90%, and a capacity retention rate of up to 90.22% after 200 cycles at room temperature and 0.2C, showing good initial coulombic efficiency and cycle performance.
[0055] The present application also provides a negative electrode sheet, comprising a current collector and the above-mentioned hard carbon negative electrode material on the surface of the current collector.
[0056] The present application also provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises the negative electrode sheet mentioned above.
[0057] The sodium ion battery provided in this application, in view of the advantages of the above-mentioned hard carbon negative electrode material, improves the capacity and first coulombic efficiency of the sodium ion battery, expands the application scenarios of the sodium ion battery, and promotes the development of downstream industries.
[0058] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0059] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0060] Example 1
[0061] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0062] 1. Mix and grind food-grade cassava flour, D-galactose and dealkalized lignin in a mass ratio of 99:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0063] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 5 h to obtain the hard carbon negative electrode material of Example 1.
[0064] Example 2
[0065] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0066] 1. Mix and grind food-grade cassava flour, D-galactose and dealkalized lignin in a mass ratio of 95:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0067] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 5 h to obtain the hard carbon negative electrode material of Example 2.
[0068] Example 3
[0069] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0070] 1. Mix and grind food-grade cassava flour, D-galactose and dealkalized lignin in a mass ratio of 99:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0071] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 7 h to obtain the hard carbon negative electrode material of Example 3.
[0072] Example 4
[0073] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0074] 1. Mix and grind food-grade cassava flour, D-galactose and dealkalized lignin in a mass ratio of 99:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0075] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 20 h to obtain the hard carbon negative electrode material of Example 4.
[0076] Example 5
[0077] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0078] 1. Mix and grind food-grade potato starch, D-galactose and dealkalized lignin in a mass ratio of 99:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0079] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 5 h to obtain the hard carbon negative electrode material of Example 5.
[0080] Example 6
[0081] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0082] 1. Mix and grind food-grade corn starch, D-galactose and dealkalized lignin in a mass ratio of 99:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0083] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 5 h to obtain the hard carbon negative electrode material of Example 6.
[0084] Example 7
[0085] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0086] 1. Mix and grind food-grade pregelatinized starch, D-galactose and dealkalized lignin in a mass ratio of 99:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0087] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 5 h to obtain the hard carbon negative electrode material of Example 7.
[0088] Example 8
[0089] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0090] 1. Mix and grind food-grade cassava flour, D-galactose and dealkalized lignin in a mass ratio of 90:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0091] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 5 h to obtain the hard carbon negative electrode material of Example 8.
[0092] Example 9
[0093] This embodiment provides a hard carbon negative electrode material, and the preparation process is as follows:
[0094] 1. Mix and grind food-grade potato starch, glucose and dealkalized lignin in a mass ratio of 99:1:1 for 1 h to obtain a precursor with a mesh size of 300.
[0095] 2. The mixed and ground precursor material was sintered at a temperature of 1400° C. for 5 h to obtain the hard carbon negative electrode material of Example 9.
[0096] Comparative Example 1
[0097] This comparative example provides a hard carbon negative electrode material. The difference from Example 1 is that the ratio of cassava flour to D-galactose and dealkalized lignin is 85:7.5:7.5. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.
[0098] Comparative Example 2
[0099] This comparative example provides a hard carbon negative electrode material. The difference from Example 2 is that the sintering temperature is 1400° C. and the sintering time is 25 h. The remaining raw materials and methods are the same as those in Example 2 and will not be repeated here.
[0100] Comparative Example 3
[0101] This comparative example provides a hard carbon negative electrode material. The difference from Example 1 is that the sintering temperature is 900° C. and the sintering time is 5 h. The other raw materials and methods are the same as those in Example 1 and will not be repeated here.
[0102] Comparative Example 4
[0103] This comparative example provides a hard carbon negative electrode material. The difference from Example 5 is that the ratio of food-grade potato starch to D-galactose and dealkalized lignin is 89:1:1, and the remaining raw materials and methods are the same as those in Example 5, which will not be repeated here.
[0104] Comparative Example 5
[0105] This comparative example provides a hard carbon negative electrode material. The difference from Example 6 is that the ratio of food-grade corn starch to D-galactose and dealkalized lignin is 89:1:1, and the remaining raw materials and methods are the same as those in Example 6, which will not be repeated here.
[0106] Comparative Example 6
[0107] This comparative example provides a hard carbon negative electrode material. The difference from Example 7 is that the ratio of pregelatinized starch to D-galactose and dealkalized lignin is 89:1:1, and the remaining raw materials and methods are the same as those in Example 7, which will not be repeated here.
[0108] Comparative Example 7
[0109] This comparative example provides a hard carbon negative electrode material. The difference from Example 1 is that the ratio of cassava flour to D-galactose is 99:1, no dealkalized lignin is added, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.
[0110] Comparative Example 8
[0111] This comparative example provides a hard carbon negative electrode material. The difference from Example 1 is that the ratio of cassava flour to dealkalized lignin is 99:1, D-galactose is not added, and the remaining raw materials and methods are the same as those in Example 1, which will not be repeated here.
[0112] Test Case
[0113] The hard carbon negative electrode materials obtained in each embodiment and comparative example were respectively mixed with Super p, CMC, and PAAs in a mass ratio of 7:1.5:0.75:0.75, and stirred on a magnetic stirrer with water as a dispersant. After stirring for at least 8 hours, the mixture was coated and placed in an oven for 8 hours to obtain the negative electrode sheets of each embodiment and comparative example.
[0114] Metallic sodium was used as the positive electrode; the electrolyte was 1M NaPF6 / (EC+PC+DMC), in which the volume ratio of EC, PC and DMC was 1:1:1; the separator was glass fiber, and the cells were assembled into 2025 button cells in a glove box filled with argon.
[0115] The button cell was subjected to charge and discharge tests. The current was 0.2C (1C is 300mA / g) and the charge and discharge temperature was 25°C. The charge and discharge specific capacity and first cycle coulomb efficiency of the button cell were measured, and the results are shown in Table 1. The charge and discharge curves of the hard carbon negative electrode material of Example 2 of the present application are shown in Table 1. Figure 2 As shown, the 200 cycle diagram of the hard carbon negative electrode material of Example 1 of the present application is as follows Figure 3 shown.
[0116] Table 1 Electrochemical performance of sodium ion batteries of various embodiments and comparative examples
[0117]
[0118]
[0119] According to Table 1, the present embodiment of the present invention mixes starch raw materials with sugars and lignin and performs a suitable sintering process. The charge-discharge specific capacity and the first-cycle coulomb efficiency of the obtained hard carbon negative electrode material are better than those of the comparative example, and the starch raw materials do not expand during sintering, and the carbon yield is high. In the present embodiment of the present invention, starch is used as raw material, so that its production cost is low and it is easy to obtain; a small amount of sugar is used for coating, because sugar has a high specific surface area, pore structure and conductive properties, it can provide more energy storage space and fast ion transmission channels; a small amount of lignin can increase the reaction rate and improve the stability of the hard carbon material.
[0120] Compared with Examples 1-9, Comparative Examples 1 and 4-6 show that the hard carbon negative electrode material of the present application cannot be obtained if the amount of starch raw material added is too high or too low; Comparative Examples 2-3 show that the hard carbon negative electrode material of the present application cannot be obtained if the sintering temperature is too high or too low; Comparative Examples 7-8 show that the modification effect of the present application cannot be achieved if the starch raw material is only mixed with sugars or lignin alone.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0122] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a hard carbon negative electrode material, characterized in that: include: The starch raw material is mixed with sugar and lignin and ground to obtain a precursor; The precursor is sintered to obtain a hard carbon negative electrode material.
2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The sugars include monosaccharides and / or disaccharides; the sugars include at least one of D-galactose, glucose, fructose, sucrose and lactose.
3. The method for preparing a hard carbon negative electrode material according to claim 1 or 2, characterized in that: The mass ratio of the starch raw material, the sugar and the lignin is (90-99):(1-5):(1-5).
4. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The mixing and grinding time is 1 h to 2 h; and / or the particle size of the precursor is 80 mesh to 400 mesh.
5. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The sintering temperature is 1000° C. to 1600° C., and the sintering time is 5 h to 24 h.
6. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The starch raw material includes at least one of potato starch, corn starch, cassava flour and pregelatinized starch; and / or the lignin is dealkalized lignin.
7. A hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material is prepared by the preparation method of any one of claims 1 to 6.
8. A negative electrode sheet, characterized in that: Comprising the hard carbon negative electrode material as described in claim 7.
9. A sodium ion battery, characterized in that: Includes the negative electrode sheet as described in claim 8.
10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.